Contemporary Patriotism in School Education ? Assumptions of Core Curricula - Kopińska, Violetta; Majchrzak, Kinga; Szwech , Agata (INSTED: Interdisciplinary Studies in Education & Society, 2017)
Taking into account the nature of the phenomena and processes that determine the specificity of the contemporary world one can conclude that (from the pedagogical point of view) it is important to prepare individuals to be contemporary patriots during the course of formal education. A contemporary patriot is a multidimensional patriot who is ready to accept responsibility for a community in a broad sense (not excluding anyone from this community) and being critical towards history, but at the same time maintaining the respect for the heritage of ancestors and being tied to his/her nation. What was searched for in the presented study is the answer to the following question: do the core curricula of school education assume achieving the learning outcomes which are essential for the development of contemporary patriotism? The research sample consisted of core curricula for all stages of education. The results of the research do not allow, however, to establish that the learning outcomes included in core curricula go beyond the classical understanding of patriotism and promote its contemporary form. The research has been conducted within the project Improving Teaching Methods for Europe funded by the EU program Erasmus + Strategic Partnerships.